Migrant and Seasonal Head Start Study, United States, 2017-2018 - Caswell, Linda ([Verlag nicht ermittelbar], 2019)
In 2015, the Administration for Children and Families funded a new study - the Migrant and Seasonal Head Start Study (MSHS Study) - to focus on MSHS programs and the families they serve. The MSHS Study was designed to closely match the characteristics of the whole population of MSHS programs, centers, families, and children across the United States (a "nationally representative study"). Since the last nationally representative study of MSHS was conducted almost 20 years ago, this study provided an update on MSHS programs and centers, as well as the migrant and seasonal farmworker families they serve. The MSHS Study included data from programs and centers (collected from surveys of program and center directors), classrooms (collected through classroom observations and from surveys of teachers and assistant teachers), families (collected from interviews with parents), and children (collected from direct assessments, assessor ratings, and parent and teacher ratings of children). Although the study gathered a range of program, practice, and family information, a central theme of the data collection focused on language practice and the language skills and abilities of the children served. The study examined the following research questions: What are the characteristics of MSHS programs, centers, staff, families, and children? What services does MSHS provide, and what are the instructional practices and general classroom quality of MSHS classrooms? What are the associations between MSHS characteristics and child/family well-being? The MSHS Study methodology, sample, and measures were all developed (or selected) in collaboration with MSHS stakeholders and experts in MSHS programs and early childhood research. The study was conducted by Abt Associates and its partners - the Catholic University of America and Westat - under contract to the Office of Planning, Research, and Evaluation, Administration for Children and Families, U.S. Department of Health and Human Services. This collection is organized into 18 data parts: 4 files with data from MSHS staff surveys, including surveys with program directors (DS2), center directors (DS4), teachers (DS7), and assistant teachers (DS8). All staff surveys collected information on the respondent's background and experience and then focused on questions relevant to each respondent. For example, the Program Director Survey collected information on issues such as enrollment, program policies, and approaches to hiring, communication, and supervision. The Center Director Survey focused on characteristics of the center, such as staffing, enrollment, family engagement, and instructional practices. The Teacher and Assistant Teacher Surveys gathered information on topics at the classroom level, such as classroom composition and language(s) of instruction, and also included the 12-item version of the Center for Epidemiologic Studies Depression Scale. 1 file with data from classroom observations (DS6), including items from the Classroom Assessment Scoring System (CLASS) Pre-K, Early Language and Literacy Classroom Observation-Dual Language Learners (ELLCO-DLL), and the MSHS Cultural Items and Language Use (CILU) Checklist. 5 direct child assessments, including height and weight measurements (DS10), the Leiter-3 Examiner Rating Scale (DS11), the Preschool Language Scales Fifth Edition (PLS-5) - English (DS12), the PLS-5 - Bilingual (DS13), and the Woodcock Muñoz Language Survey (DS14). 1 file with data from the Ages and Stages Questionnaire (DS15) completed by teachers for infants and young children to assess children's nonverbal and verbal communication skills. 1 file for Teacher Report of Child (DS16), including data from children's language dominance and proficiency, questions about delays and disabilities, the MacArthur-Bates Communicative Development Inventory (CDI-English)/Inventario del Desarrollo de Habilidades Comunicativas (IDHC-Spanish), Early Childhood Longitudinal Study (ECLS)-Birth Cohort questions on counting in English and Spanish, and ECLS-Kindergarten Approaches to Learning. 1 file for Parent Report of Child (DS17), including data from the MacArthur-Bates CDI-English/IDHC-Spanish, Brief Infant-Toddler Social and Emotional Assessment, and the ECLS-B Socioemotional Scale. 1 file with data from the Parent Interview (DS18) that focused on characteristics of the household and focal child. The interview also included items from the Center for Epidemiologic Studies Depression Scale and the Migrant Farmworker Stress Inventory. 4 survey control files, which include the disposition code for each sampled program (DS1), center (DS3), classroom (DS5), and child/parent (DS9), as well as the base sampling weights and some additional sample information. Various demographic information, such as age, sex, marital status, race, and ethnicity, is also included in the data.